If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -5) = 5x + -20 Reorder the terms: 5(-5 + x) = 5x + -20 (-5 * 5 + x * 5) = 5x + -20 (-25 + 5x) = 5x + -20 Reorder the terms: -25 + 5x = -20 + 5x Add '-5x' to each side of the equation. -25 + 5x + -5x = -20 + 5x + -5x Combine like terms: 5x + -5x = 0 -25 + 0 = -20 + 5x + -5x -25 = -20 + 5x + -5x Combine like terms: 5x + -5x = 0 -25 = -20 + 0 -25 = -20 Solving -25 = -20 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| k-39=-16 | | 12+2x=-3+x | | 6+17x-1=9x+47-6x | | 3.501+x=21 | | x^3-2x^2+49x-98=0 | | 2x+9y=xy | | 2/x=10/5 | | -81=9r | | 3.2+.17x=5.75 | | 64-c^3= | | X^2-(1/2)x-9 | | 6.3+x=7 | | -1-7x=-2x+4 | | 2c^2-c-1=0 | | x-16.2=23.3 | | 2r+2s=50 | | -1(x+2)-4=1(x-3) | | -3(n-5)=3(1-3n) | | -3(4p+2)-2(3-11p)-3(4+3p)=0 | | -u+206=96 | | 2x=7+3y | | 170=270-w | | 13x-6x=5(x-3) | | 24+8x=8(5x+8)+8x | | 9t=45 | | 8w+65= | | 9x-3-(x-3)=5 | | -2(-7n-8)=-39+3n | | 8w-65= | | 5.2X-3=4.2X | | 5(X-3)+1=-8(X-1) | | 7x-1=4(-x+3) |